2011
DOI: 10.1186/1476-511x-10-130
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of n-3 PUFA and γ-linolenic acid in blood lipids and red blood cell lipids together with their influence on disease activity in patients with chronic inflammatory arthritis - a randomized controlled human intervention trial

Abstract: Background and aimMarine n-3 fatty acids and γ-linolenic acid both have anti-inflammatory effects and may be useful to help treat inflammatory diseases. The effects of these alone or combined were examined in patients with arthritis in a randomized controlled trial.DesignPatients with rheumatoid arthritis or psoriatic arthritis were randomized into four groups in a double-blind, placebo-controlled parallel designed study. Patients received the respective capsules (1: 3.0 g n-3 LC-PUFA/d; 2: 3.2 g γ-linolenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 45 publications
1
29
1
3
Order By: Relevance
“…As well, intake of 3 g of n -3 PUFA markedly increases the AA/EPA ratio and EPA + DHA index, which are highly reliable predictors of sudden cardiac death [50,51,52]. This is an added value, since patients with RA have strongly elevated risk of cardiac death [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…As well, intake of 3 g of n -3 PUFA markedly increases the AA/EPA ratio and EPA + DHA index, which are highly reliable predictors of sudden cardiac death [50,51,52]. This is an added value, since patients with RA have strongly elevated risk of cardiac death [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…6 In a recent randomized controlled trial 23 involving 54 rheumatoid arthritis (RA) and six psoriatic arthritis patients who received 12 weeks treatment with n-3 PUFA, they analyzed the proportion of EPA and DHA being incorporated into the erythrocyte membranes. They have concluded that n-3 PUFA resulted in an increased incorporation of the eicosanoid precursor fatty acids (EPA, DHA) in plasma lipids and cell membranes, which had a positive correlation with a significant reduction of disease activity parameters (Disease Activity Score of 28 joints, VAS scale) in RA.…”
Section: Discussion Summary Of Main Resultsmentioning
confidence: 99%
“…The n À 3 long-chain PUFA and GLA were found to affect the incorporation of eicosanoid precursor fatty acids (EPA, DHA, DGLA) in plasma lipids and cell membranes, and there was an improvement in the patients' clinical status. In addition, n À 3 long-chain PUFA improved CV risk factors such as the AA/EPA ratio and the n À 3 fatty acid index [48]. The DAS28 composite activity index tended to fall in the group receiving 3 g olive oil/day.…”
Section: Clinical Trial On Mediterranean Diet Components Supplementatmentioning
confidence: 98%